PELATIHAN PENGGUNAAN PLATFORM APLIKASI E-LEARNING SCHOOLOGY PADA GURU SMA - Salim Salim; La Ode Ahmad Jazuli; Nurhayati Nurhayati; Hendra Nelva Saputra (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
The purpose of this devotion is to increase knowledge and insight into the innovation of e-learning based learning for teachers of SMA Negeri 4 Kendari can be done through training activities in the application of Schoology. This activity was attended by 15 people in the teachers of SMA Negeri 4 Kendari with the implementation method of devotion using lecture methods, questions and answers, and simulations. The results of this dedication show that (1) the trainees have a knowledge of the use of e-learning application Platform Schoology, (2) The trainees already have a learning class using the platform E-Learning Application Schoology, and (3) The trainees have been knowledgeable in creating and developing the content of e-learning Schoology application